Hematological Profile in COVID-19, Whether It Matters in Children - Purnima Margekar; Ashok Kumar; Venu Gopal Margekar; Shubha Laxmi Margekar (Indian Journal of Medical Specialities)
Coronavirus disease 2019 (COVID-19) is an acute respiratory and systemic illness, and is a public health emergency which has involved all the continents. Though limited data is available for infection in pediatric population, infection seen in children is of milder form. During this pandemic, documentation of laboratory predictors to discriminate between mild and severe forms of this infection would be helpful. Various hematological parameter alterations in the pediatric COVID-19 cases show anemia, thrombocytopenia, eosinopenia, and inconsistent leukocyte indices. It may be too early to say right now as to what extent will these alterations help us in outlining the severity of disease or transmission of disease. However, it will be pertinent to understand these abnormalities, and keep track of them, so as to understand the disease, as the pandemic unfolds.